2006
DOI: 10.1111/j.1365-2929.2006.02467.x
|View full text |Cite
|
Sign up to set email alerts
|

Making sense of qualitative data analysis: an introduction with illustrations from DIPEx (personal experiences of health and illness)

Abstract: Qualitative analysis of patients' perspectives of illness can illuminate numerous issues that are important for medical education, some of which are unlikely to arise in the clinical encounter. Qualitative studies can also cover a much broader range of experiences - of both common and rare disease - than clinicians will see in practice. The DIPEx website is based on qualitative analysis of collections of interviews, illustrated with hundreds of video and audio clips, and is an innovative resource for medical e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
431
0
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 496 publications
(437 citation statements)
references
References 14 publications
0
431
0
6
Order By: Relevance
“…The qualitative data was read multiple times by researchers (KT, LB and PM) and analysed using the 'one sheet of paper' (OSOP) method [15]. Themes were examined across the whole dataset and in the context of individual responses.…”
Section: Questionnaire Analysismentioning
confidence: 99%
“…The qualitative data was read multiple times by researchers (KT, LB and PM) and analysed using the 'one sheet of paper' (OSOP) method [15]. Themes were examined across the whole dataset and in the context of individual responses.…”
Section: Questionnaire Analysismentioning
confidence: 99%
“…The One Sheet of Paper method (OSOP) was used to summarize the data captured under particular themes in order to help identify patterns or common language used [51]. For example, under the broad theme of 'psychological problems', it was identified that psychological difficulties commonly manifested later on.…”
Section: Discussionmentioning
confidence: 99%
“…A 'grounded theory'-based analytical approach was used to prioritise interviewees' perspectives and experiences. Stage one was 'immersion' in the data to identify themes (Pope and Mays, 2000;Ziebland and McPherson, 2006) through field notes, transcribing and editing interviews, reading and re-reading interviews, and producing interviewee vignettes. Emergent themes were prioritised, although themes reflecting the research aims, such as reasons for non-participation, were additionally sought (Seale and Kelly, 1998).…”
Section: Methodsmentioning
confidence: 99%